Petrographic and geochemical study of the Jarosite bearing layers of Aeolian Islands - Khyabani, Fahimeh Ryazi; Pantano, Pietro Salvatore; Barca, Donatella; Crisci, Gino Mirocle (My University, 2014)
A thin reddish-brown Surface Coating (SC) layer has diffusely covered many outcrops of Vulcano Island (one of the Aeolian Islands), located in the Tyrrhenian Sea, south Italy. Vulcano, in the last 120ka has been subjected to volcanic activities including both eruptions (pyroclastic and lava types in shoshonitic and leucite-tephritic series) and fumarolic degassing. The SC that has been formed on almost all these lithologies appears as a reddish (sometimes pinkish) brown glass-like rind with a greasy luster which adheres to substratum and fills and completely seals its surface irregularities. The precise formation process of the SC is what we have tried to model in the present work. The SC in Vulcano, like other active volcanic precincts, includes amorphous silica associated with a sulfate phase as jarosite mineral. Jarosite as a basic hydrous sulfate of potassium and iron is the head member of jarosite subgroup. Under the microscope, SC is consisted of a micro laminated layer (less than 1μm to 7μm in thickness) which is composed of alternative dark and light laminae. The light laminae are composed of jarosite, while the darker ones are made of almost pure silica. In many cases of the SC, the laminae encompass lenticular areas containing coarser mineral crystals and noticeable number of glass shards, very fresh to altered in different grades, within an inexplicit background. The relations between all these components (laminated portion and the trapped area between different subsets of laminae) creates some particular textures such as lentic/eye texture; convoluted texture (flow of laminae); branching, rejoining, and tee-shaped perpendicular junctions of the laminae. These particular textures are quite comparable to the patterns of Liesegang Bands in the microscopic scale. Permeability of the rock; the presence of reactants such as oxygen, iron, and sulfur; and a potential fluid to be supersaturated are required factors for developing the Liesegang bands. The porous surface of the pyroclastic deposits of Vulcano can be exposed to the acidic fluids (produced by the interaction between water and fumarolic gases) and the availability of the iron and sulfur can provide the suitable condition to form the Liesegang patterns.
PhD School in Science, Communication and Technologies, Earth Sciences Curriculum, Ciclo XXVII, a.a.2014
Keywords: Petrologia; Petrografia